Working in higher education international affairs : understanding perceptions of organizational structure and experiences with change - Tornier, Lisa-Sophie (2018)
Internationalization arrived in higher education a long time ago. Student mobility is one aspect of this phenomenon, which is facilitated by international affairs staff in higher education institutions. As research to date has paid little attention to this topic, this study investigates the organizational structure as to international affairs staff in a university in Scandinavia to understand and initiate a discussion on the topic. In addition, an organizational change relevant for the staff was examined. To answer the research questions, an inductive and qualitative research method was chosen. From the university, 12 staff members who are involved in international affairs were interviewed individually or in pairs. The participants presented their perspectives on the organizational structure and their experiences with the structural change occurring during data collection. The data was analysed using thematic analysis. A result of the study is that the participants have similar perspectives on the organizational structure. They displayed positivity towards the existing structure in international affairs with some aspects that could be improved. However, the interviewees expressed different opinions concerning the change process, which can be placed on a continuum. While the Head of Internationalization sees the change optimistically, the international coordinators in the faculties have a rather negative perspective on the change. The International Office staff expressed both views. The findings can be used as a basis for deeper research to better understand organizational structures in international affairs at higher education institutions and how leading change processes can be improved regarding involved staff.